The Digital Body: Telegraphy as Discourse Network. (January 2015) - Maddalena, Kate; Packer, Jeremy
This article considers the use of flag telegraphy by the US Signal Corps during the Civil War as it functioned as a proto-technical medium that preceded wire telegraphy as a military communications technology. Not only was flag telegraphy a historical step towards contemporary technical media, it was also an early iteration of the digitization of communication. Our treatment ties together three main theoretical threads as a way of seeing 'the digital' in material communication practices: (1) Friedrich Kittler's concept of technical media as a remediation between the 19th and 20th centuries, (2) Foucault's docile bodies as means of reproducing culture, and (3) James Carey's argument that the telegraph reconfigured communication. The Signal Corps is a rich historical moment in terms of media history and history of technology because it illustrates the convergence of historical exigencies at work in the war machine: mobility, secrecy, precision, and speed. Each contributes, we argue, to a digital telos that privileges digital ways of knowing and being.